Film dokumentalny Akcja T4, lekarze w służbie nazizmu jako medium pamięci protetycznej - Pawelczak , Katarzyna (Studia Edukacyjne, 2023)
Prosthetic memory refers to memories acquired because of the personal experience of receiving audiovisual and multisensory products of mass culture (Skalska, 2014, p. 343). The article attempts to answer the question of whether a documentary narrating a silenced event with no full representation, can function as a medium of prosthetic memory? I attempt to indicate how the film structure of Action T4, A Doctor Under Nazism (dir. Catherine Bernstein, 2014) can generate the experience of events getting blurred in communicative memory and not yet fixed in cultural memory. Is the bricolage structure of the film narrative, engaging the viewer’s attention and emotions, capable of bringing back from oblivion those who had to die because they were deemed unworthy of life, i.e. psychiatric hospital patients and persons with disabilities? Can a documentary film, by evoking facts affected by amnesia and pushed out of memory, manage to turn the traces of the absence of the victims of Action T4 into a m e m o r y that, at least for a moment, will restore their indispensable human dignity?